Resource scheduling strategy based on simulated annealing algorithm in hybrid D2D cellular networks - Xiang YU; Haibo ZHANG; Lu YANG (Dianxin kexue)
D2D communication is a short distance communication mode in the future 5G network.In the process of communication,the information is transmitted from the sender to the receiver directly,without the need to transmit through the base station.The introduction of D2D communication in the traditional cellular network can greatly improve the total throughput of the system,increase the utilization of spectrum resources and reduce the power consumption of the transmitter.A resource allocation method which was used in hybrid D2D cellular network was mainly introduced,spectrum resources was distributed by Lagrange multiplier method combined with simulated annealing algorithm,a consideration of channel capacity and energy consumption of the resource scheduling strategy based on simulated annealing algorithm was put forward.This algorithm was simulated by the simulation platform in Vienna,compared to the traditional greedy optimization algorithm,it can significantly increase the total system throughput and bandwidth utilization and reduce the power consumption.In addition,the distributed algorithm was adopted,that D2D users searched for a suitable target channel and calculated their transmit power according to the algorithm steps,which reduced the signaling overhead of the base station.